2023
DOI: 10.1186/s12957-023-03101-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of matrix metalloproteinase-9 expression in papillary thyroid carcinoma: a meta-analysis

Abstract: Objective The purpose of this study was to investigate the relationship between the expression of matrix metalloproteinase-9 (MMP-9) and pathological indexes in papillary thyroid carcinoma (PTC). Evidence obtained The database was searched in PubMed, Embase, CNKI, and Web of Science databases for relevant clinical trials. The odds ratio (OR) and 95% confidence interval (CI) show the effect of MMP-9 expression and age, tumour size, gender, lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Studies have analyzed MMP9 protein and mRNA levels in thyroid tissues using immunohistochemistry, enzyme-linked immunosorbent assay (ELISA), gelatin zymography, Western blotting, and polymerase chain reaction (PCR). Most report significantly higher MMP9 expression in thyroid cancer specimens than in normal tissues or benign nodules [21,[61][62][63][64][65][66][67][68][69][70][71]. Our metaanalysis showed that high MMP9 level is prevalent in 69% (95% CI: 62-77%) of PTC tissue specimens (Figure 11A).…”
Section: Mmp9 and Mir-145 Expression In Thyroid Cancermentioning
confidence: 93%
See 3 more Smart Citations
“…Studies have analyzed MMP9 protein and mRNA levels in thyroid tissues using immunohistochemistry, enzyme-linked immunosorbent assay (ELISA), gelatin zymography, Western blotting, and polymerase chain reaction (PCR). Most report significantly higher MMP9 expression in thyroid cancer specimens than in normal tissues or benign nodules [21,[61][62][63][64][65][66][67][68][69][70][71]. Our metaanalysis showed that high MMP9 level is prevalent in 69% (95% CI: 62-77%) of PTC tissue specimens (Figure 11A).…”
Section: Mmp9 and Mir-145 Expression In Thyroid Cancermentioning
confidence: 93%
“…Dragutinovic et al also found increased MMP9 immunostaining in the more poorly differentiated classical PTC subtype versus the follicular variant [81]. Higher MMP9 levels have additionally been linked to advanced TNM stage in PTC [62,65,67,80], extrathyroidal extension [21,61,64,65,75,79], and larger tumor size [62,65,67] in PTC. Clinically, MMP9 activity distinguishes between sporadic and radiation-induced PTC, with greater MMP9 expression in post-Chernobyl tumors indicating more aggressive disease [82].…”
Section: Associations With Clinicopathological Featuresmentioning
confidence: 94%
See 2 more Smart Citations